Metabolic comparison of tethered and simulated swimming ergometer exercise - Payne, W. R.; Lemon, P. W. R. (1982)
Two types of swimming auxiliary activity were analyzed for physiological responses: simulated swimming was performed on a modified ergometer using a freestyle action (alternate, cyclic arm movements), with the legs stationary; and tethered swimming was performed stationary in the water with legs tied and buoyed. Both activities were performed under similar protocols of continuous one-minute load increments. It was found that (a) tethered swimming developed significantly greater VO2max and lactate accumulation levels; (b) simulated swimming produced a greater VE/VO2; and (c) HRmax and VEmax did not differ between the conditions. Implication: Despite the apparent similarities of HRmax, VEmax, and subjective assessments of effort expended, as well as popular usage of these two activities, energy requirements, at least during maximal exercise, are quite different. This poses a problem for coaches. If both are deemed to be useful, but their energy use is very different, which one is correct and which is incorrect for swimming? It is also highly likely that neither is appropriate for specific swimming enhancement.